New finding of Rhadinoloricaria macromystax (Siluriformes: Loricariidae): redescription of the genus and description of a new species from Ecuador - Provenzano-Rizzi, Francisco; Barriga-Salazar, Ramiro (Zootaxa, 2020)
The fish collection from the Museum of Escuela Politécnica Nacional, Quito, Ecuador, has nine lots with 12 specimens assigned to genus Rhadinoloricaria. Specimens come from the Napo and Pastaza rivers, Amazon River basin, eastern Ecuador. One specimen matches accurately with figures and original description of Loricaria macromystax Günther, 1869, type species of Rhadinoloricaria. After 150 years, this is the first secure identification of the species, which allowed an accurate description of the genus Rhadinoloricaria, and the discovery of a new species from Ecuador, described herein. In addition, using available specimens, figures and literature, a comparative analysis on external morphology was performed among the eight species included in Rhadinoloricaria. The analysis documented significant differences between them, in some morphological external characters and in buccal ornamentation. The results suggest that the eight species can be grouped into three or four genera. Rhadinoloricaria, in strict sense, has two species. Apistoloricaria is considered a valid genus, and include the four species previously assigned to it. Rhadinoloricaria bahuaja and R. rhami do not belong to the known genera in the Pseudohemiodon group. At this time, available data suggests that both species could continue included in ‘Rhadinoloricaria’, waiting further analyses to solve their generic status. Results support the use of buccal ornamentation patterns alone or combined with some morphological characters as valuable tool for generic identification within Loricariini.